Interface self-assembly of plasmonic nanolayer for sensitive detection of heavy metals in water using NELIBS - Yuying Zhu; Yuanchao Liu; Siyi Xiao; Chen Niu; Condon Lau; Zhe Li; Zebiao Li; Binbin Zhou; Zongsong Gan; Lianbo Guo (Nano Materials Science)
Nowadays, high-stable and ultrasensitive heavy metal detection is of utmost importance in water quality monitoring. Nanoparticle-enhanced laser-induced breakdown spectroscopy (NELIBS) shows high potential in hazardous metal detection, however, encounters unstable and weak signals due to nonuniform distribution of analytes. Herein, we developed an interface self-assembly (ISA) method to create a uniformly distributed gold nanolayer at a liquid-liquid interface for positive heavy metal ions capture and NELIBS analysis. The electrostatically self-assembled Au nanoparticles (NPs)-analytes membrane was prepared at the oil-water interface by injecting ethanol into the mixture of cyclohexane and Au NPs-analytes water solution. Then, the interface self-assembled Au NPs-analytes membrane was transformed onto a laser-processed superhydrophilic Si slide for detection. Three heavy metals (cadmium (Cd), barium (Ba), and chromium (Cr)) were analyzed to evaluate the stability and sensitivity of the ISA method for NELIBS. The results (Cd: RSD ​= ​3.6 ​%, LoD ​= ​0.654 ​mg/L; Ba: RSD ​= ​3.4 ​%, LoD ​= ​0.236 ​mg/L; Cr: RSD ​= ​7.7 ​%, LoD ​= ​1.367 ​mg/L) demonstrated signal enhancement and high-stable and ultrasensitive detection. The actual sample detection (Cd: RE ​= ​7.71 ​%, Ba: RE ​= ​6.78 ​%) illustrated great reliability. The ISA method, creating a uniform distribution of NP-analytes at the interface, has promising prospects in NELIBS.